2014
DOI: 10.1182/blood-2014-03-563296
|View full text |Cite
|
Sign up to set email alerts
|

Ser70 phosphorylation of Bcl-2 by selective tyrosine nitration of PP2A-B56δ stabilizes its antiapoptotic activity

Abstract: Key Points O2− modifies B56δ at Y289 to block the PP2A holoenzyme assembly. This results in S70 Bcl-2 phosphorylation and promotes tumor chemoresistance. Primary lymphomas with low SOD1 have high B56δ tyrosine nitration and S70pBcl-2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 37 publications
(37 reference statements)
2
64
0
Order By: Relevance
“…In animals, PP2A is a well-known tumor suppressor. ROS accumulation in cancer cells causes nitration and inactivation of PP2A, which interferes with the interaction of Bcl-2 with the PP2A catalytic core, leading to increased phosphorylation and antiapoptotic activity of Bcl-2 [38]. We recently reported that V .…”
Section: Discussionmentioning
confidence: 99%
“…In animals, PP2A is a well-known tumor suppressor. ROS accumulation in cancer cells causes nitration and inactivation of PP2A, which interferes with the interaction of Bcl-2 with the PP2A catalytic core, leading to increased phosphorylation and antiapoptotic activity of Bcl-2 [38]. We recently reported that V .…”
Section: Discussionmentioning
confidence: 99%
“…We co-localized LMO4 and nitrotyrosine in the outer hair cells, which are primary targets of cisplatin-induced ototoxicity [4]. Protein nitration can modulate phosphorylation cascades, alter protein function, and facilitate proteolytic degradation of nitrated proteins [28], [29], [30], [31], [32], [33], [34]. Consistent with these reports, cisplatin-induced nitration of LMO4 was associated with a significant decrease in its protein levels, not only in the auditory cells, but in the renal and neuronal cells, which are also susceptible to the toxic side-effects of cisplatin [35].…”
Section: Introductionmentioning
confidence: 99%
“…It could directly disrupt the Bcl‐2/Bax association to liberate Bax from the heterodimer complex . In Drosophila, knock down or loss of either of the subunits A, C, or B56 leads to hyper phosphorylation of Bcl‐2, thus initiating p53‐mediated apoptosis . The purpose of this study was to evaluate JS‐K as a cutative agent for HCC.…”
Section: Discussionmentioning
confidence: 99%